The female in Aristotle's biology : reason or rationalization - Mayhew, Robert (University of Chicago Press, 2004)
While Aristotle's writings on biology are considered to be among his best, the comments he makes about females in these works are widely regarded as the nadir of his philosophical oeuvre. Among many claims, Aristotle is said to have declared that females contribute nothing substantial to generation; that they have fewer teeth than males; that they are less spirited than males; and that woman are analogous to eunuchs. In The Female in Aristotle's Biology, Robert Mayhew aims not to defend Aristotle's ideas about females but to defend Aristotle against the common charge that his writings on fema.